P-165 Can acoustic trauma be considered an accident at workplace?. (14th March 2023) - Ayed, Wiem; Mersni, Mariem; Youssef, Imen; Mechergui, Najla; Bahri, Ghada; Brahim, Dorra; Said, Hanen Ben; Ladhari, Nizar
Abstract : Introduction: Acoustic trauma exists in the workplace and its evolution can be spontaneously favorable as well as serious. Aims: Demonstrate the different aspects of ear injuries that have been considered as accidents at work. Methods: Retrospective cross-sectional study of patients with work-related injuries who consulted the Occupational Medicine Department at the Charles Nicolle Hospital over a six-year period from January 2016 to November 2022. Results: We have collected eleven cases of patients with atrial trauma. The average age was 41±10 years. They were all male with a mean age of 41±10 years [28–58]. The patients were employed as police officers (n=6), workers (n=3), doctor (n=1), and welder(n=1). The patients were victims of a work-related accident of the following types bomb explosion (n=5), a fall from one's own height (n=3), exposure to excessive noise (n=2), exposure to gunfire (n=1), a commuting accident (n=1), and a fall of a metal object in the temporal region of the cranium (n=1), which resulted in perforation of the eardrum in five patients. Hearing deficits were noted in all patients sensorineural hearing loss (n=7), mixed hearing loss (n=4), conductive hearing loss (n=1), and cophosis (n=2). The associated symptoms were hearing loss (n=7), tinnitus (n=4), otalgia (n=6), and ringing in the ears (n=3). The calculated average hearing loss was 31±17 dB [7.5–60] for the left ear and 36±14 dB [12–60] for the right ear. All cases of acoustic trauma were considered to be work-related. Six patients received compensation and the average of permanent partial disability rate was 20±7% [12–30]. Conclusion: According to our study, ear injuries can even lead to a permanent loss of hearing. A re-evaluation of medical fitness for work is sometimes necessary.